Impact Of Erp and Firm Size on Performance: The Role of Organizational Capabilities - Ainy, Wulan Nur; Harris, Lutfi (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2025)
The business digitalization era has made many companies, including those in the consumer goods sector, adopt information technologies, one of which is Enterprise Resource Planning (ERP). Implementing the ERP system in the company's operational activities, in addition to company size, is anticipated to affect company performance. The process of company adaptation to digital transformation makes organizational capabilities considered to affect company performance. This study, as such, aims to analyze the effect of ERP system implementation and company size on the performance of consumer goods companies listed on the Indonesia Stock Exchange (IDX) for the 2020-2023 period, with organizational capabilities as a moderating variable. The results of this correlational quantitative study exhibit that the ERP system implementation and company size affect company performance. Moderation results show that organizational capabilities strengthen the relationship between the ERP system implementation and company performance but cannot moderate the relationship between company size and performance.